2016
DOI: 10.3758/s13415-016-0438-z
|View full text |Cite
|
Sign up to set email alerts
|

How personal standards perfectionism and evaluative concerns perfectionism affect the error positivity and post-error behavior with varying stimulus visibility

Abstract: Error detection is required in order to correct or avoid imperfect behavior. Although error detection is beneficial for some people, for others it might be disturbing. We investigated Gaudreau and Thompson's (Personality and Individual Differences, 48, 532−537, 2010) model, which combines personal standards perfectionism (PSP) and evaluative concerns perfectionism (ECP). In our electrophysiological study, 43 participants performed a combination of a modified Simon task, an error awareness paradigm, and a maski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
(71 reference statements)
3
12
0
Order By: Relevance
“…Behavioural findings. Similar to previous studies ( Stahl et al , 2015 ; Drizinsky et al , 2016 ), we found no perfectionism-related variations in error rates or general response speed. However, high-PS perfectionists responded more slowly than the low-PS perfectionists after error trials but not after correct trials .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Behavioural findings. Similar to previous studies ( Stahl et al , 2015 ; Drizinsky et al , 2016 ), we found no perfectionism-related variations in error rates or general response speed. However, high-PS perfectionists responded more slowly than the low-PS perfectionists after error trials but not after correct trials .…”
Section: Discussionsupporting
confidence: 91%
“…In summary, these and other electrophysiological findings ( Pieters et al , 2007 ; Tops et al , 2013 ; Stahl et al , 2015 ; Drizinsky et al , 2016 ) pointed towards potentially crucial differences in error-related neural mechanisms in perfectionism subtypes. Here, we investigated perfectionism-related variations in response monitoring using functional magnetic resonance imaging (fMRI).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The Pe is thought to reflect conscious awareness of error commission (51), as the Pe is much more prominent for conscious errors versus unconscious errors (52). Pe amplitudes are also positively correlated with perfectionistic characteristics, such as high personal standards or high evaluative concerns, but these findings have not always been consistent (45,53). Other studies have shown that blunted Pe amplitudes are related to higher levels of perfectionism (54), again suggesting mixed results when examining the Pe and perfectionism.…”
Section: Introductionmentioning
confidence: 91%
“…Other studies have shown that blunted Pe amplitudes are related to higher levels of perfectionism (54), again suggesting mixed results when examining the Pe and perfectionism. Due to the wide variety of sample sizes in research to date (n=43 (53); n=94 (45); n=17 (54)) larger-scale studies across a range of perfectionistic tendencies are needed in order to further understand the relationship between perfectionism and the Pe.…”
Section: Introductionmentioning
confidence: 99%